Evaluation Nutritients Of Rice Bran Second Quality Fermented Using Rumen Fluid - ayu afria ulita ermalia (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
Rice bran is agriculture waste that easy to find. Means to increase biological value of rice bran can do with decrease of highly crude fiber. Treatment that to do with fermentation use rumen fluid from cows. Rumen fluid potential is easy to find in slaughterhouse, this rumen fluid much to never utilization. This purpose of the research for evaluation of rice bran nutrition value that fermentating used rumen fluid, with different levels and long time incubations for get lower crude fiber and higher crude protein content. Methods of this research used Laboratory experiments with Factorial-Random Complete Design 4x4 and 6 repetitions. First factor is rumen fluid levels (0, 30, 40, 50 %/w) and second factor is long incubations (0, 24, 48, 72 hours). This result of ANOVA analysis to show that increment rumen fluid levels and long incubations on rice bran fermentating process can decrease Dry Matter, Organic Matter, Crude Fiber, NDF, ADF and NDR content; as well as increase Crude Protein content but not increase Crude Fat content. The best interaction between rumen fluid levels and long time incubations is 30 %/w with 72 hours long time incubations, with 10.28±0.1 % of Crude Protein, 6.46±0.07 of Crude Fat and 22.31±0.4 of Crude Fiber content.